Allocation of health resources according to the type and size of Iranian governmental hospitals. - Sa Hassani; M Abolhallaje; S Inanlo; H Hosseini; K Pourmohammadi; P Bastani; M Ramezanian; A Barati Marnani (Tehran University of Medical Sciences, 2013)
Due to consuming about 50%-80% of health resources, hospitals are the greatest and costly operational units in Iranian Health system. so allocation of resources specially human and space resources as the most expensive ones is really important for further controlling of costs, analysis of costs and making suitable policies for increasing the profitability and allocation of resources and improvement of quality.This paper intends to describe and analyze any allocation of resources in 530 university hospitals in Iran. The final goal of this research is to provide a data bank according which there is a basis for more scientific budget allocation of state's hospitals from the size and type of application points of view.The relevant index of person to bed was 2.04 for human resources. All hospitals more than 300 beds are located in benefiting areas from which 17 cases are educational and 2 cases are therapeutic. This is necessary to mention that the rate of management group forces to total personnel at deprived areas is about 2.5% more than benefiting areas.Because 60-80% of hospital costs are applied for human forces, all managers of hospitals are obliged to revise their policies in attraction and employment of human force in order to benefit from such a valuable resource and prevent from expensive costs. So any employment of personnel should be based upon real needs of hospital.